CORRELATION BETWEEN POST-TRAUMATIC AMNESIA AND COGNITIVE FUNCTION IN PATIENTS WITH MILD HEAD INJURY (COMMOTIO CEREBRI) - Al-Kahfi, Muhammad; Suherman, Suherman; Marlia, Ika; Syahrul, Syahrul; Emril, Dessy Rakhmawati (MNJ (Malang Neurology Journal), 2026)
Background: Mild head injury (commotio cerebri) due to the direct impact of an impulsive force on the head results in temporary changes in mental status. Post-traumatic amnesia (PTA) plays an important role in predicting cognitive impairment in patients with head injury Objective: This study aimed to assess the relationship between PTA and cognitive function in patients with commotio cerebri at Dr. Zainoel Abidin General Hospital (RSUDZA) in Banda Aceh, Indonesia.. Methods: This cross-sectional observational study recruited 50 patients with mild head injury who were hospitalized in the Neurology Department of RSUDZA between January and March 2025 using consecutive sampling. PTA was assessed using the Galveston Orientation and Amnesia Test-8 (GOAT-8) questionnaire, and cognitive function was evaluated using the Indonesian version of the Montreal Cognitive Assessment (MoCA-INA). Results: The relationship between PTA and cognitive function was assessed using Spearman's correlation test. Statistical significance was set at p<0.05. A strong positive correlation was observed between PTA and cognitive function (p=0.000; r=0.618). Significant relationships existed between commotio cerebri and executive functioning (p=0.000, r=-0.521), naming (p=0.020, r=-0.327), attention (p=0.011, r=-0.357), and memory (p=0.000, r=-0.486). PTA showed significant relationships with memory (p=0.000, r=-0.51), orientation (p=0.000, r=-0.53), abstraction (p=0.011, r=-0.31), and language (p=0.020, r=-0.28). PTA was significantly correlated with cognitive impairment and executive components (p=0.000), attention (p=0.000), and memory (p=0.002). Conclusion: Cognitive impairments after traumatic brain injury include attention deficits, memory loss, and impaired executive functioning. Executive functioning and repetition are the most vulnerable areas in patients with mild head injury. PTA assessments should be conducted immediately after head trauma, as subsequent assessments are inadequate.